2003
DOI: 10.1017/s0952523803203035
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of the photoresponse in Limulus ventral photoreceptors by protein kinase C precedes rhabdomere disorganization and endocytosis

Abstract: Limulus photoreceptors utilize the phosphoinositide pathway to generate light-induced single photon events (quantum bumps) that sum to form the depolarizing receptor potential. The protein kinase C (PKC) activator, (-)-indolactam V (ILV) rapidly desensitizes the light response in Limulus ventral nerve photoreceptors. Within 10 min of extracellular application, 100 nM (-)-ILV caused a decrease in the mean amplitude of quantum bumps to 38% of control values. PKC activation by (-)-ILV also causes photosensitive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…aegypti R7 cells [3]. Rhodopsin localization within cytoplasmic compartments has been best documented for Limulus , in which movement of rhodopsin into the cytoplasm is light-triggered and serves as the mechanism for desensitization [18]. Further studies are needed to determine if similar processes occur in mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti R7 cells [3]. Rhodopsin localization within cytoplasmic compartments has been best documented for Limulus , in which movement of rhodopsin into the cytoplasm is light-triggered and serves as the mechanism for desensitization [18]. Further studies are needed to determine if similar processes occur in mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…A light-stimulated phosphorylation of the second site within loop 2, the predicted PKC site S 841 , might be expected to further reduce the affinity of LpMYO3 for actin and thereby contribute to the light trigger for the breakdown of the actin microvilli. In fact, PKC localizes to the rhabdom in Limulus ( , ) and its activation triggers rhabdom breakdown in Limulus eyes that had been “primed” by clock input (). Activation of PKC also leads to the breakdown of rhabdomeral microvilli in several other arthropods ( ).…”
Section: Discussionmentioning
confidence: 99%
“…Activators and inhibitors of protein kinase C (PKC) were shown to alter the transcription levels of the light‐regulated albino‐3 ( al‐3 ) mRNA in response to light, suggesting a role for this kinase in the inhibition of the light‐regulated gene expression. This result correlates with other studies which have identified PKCs involved in light signalling in vertebrates (Udovichenko et al ., 1996; Shiells and Falk, 2000; Dabdoub et al ., 2003), Drosophila (Hardie et al ., 1993; Scott and Zuker, 1997; Liu M. et al ., 2000) and plants (Raghuram and Sopory, 1995), where PKC was generally shown to be involved in the desensitization of the photoreceptor and therefore the adaptation to light.…”
Section: Introductionmentioning
confidence: 99%